A new cirrhotic animal protocol combining carbon tetrachloride with methotrexate to address limitations of the currently used chemical-induced models - Mansouri, Rasha A.; Ahmed, Adel M.; Alshaibi, Huda F.; Al-Bazi, Maha M.; Banjabi, Abeer A.; Alsufiani, Hadeil Muhanna; Aloqbi, Akram Ahmed; Aboubakr, Esam M. (Frontiers in Pharmacology, 2023)
Background: Chemically induced cirrhotic animal models are commonly used. However, they have limitations such as high mortalities and low yield of cirrhotic animals that limit their uses. Aims: To overcome these limitations by administering the half-commonly used doses of CCl4 and methotrexate (MTX) depending on the proposed synergistic hepto-cirrhotic effect. Methods: Rats were divided into six groups: Normal (4 weeks), Normal (8 weeks), MTX, CCl4 (4 weeks), CCl4 (8 weeks), and MTX + CCl4 (4 weeks) groups. Animals’ hepatic morphology and histopathological characterization were explored, hepatic Bcl2 and NF-κB-p65 tissue content were determined using the immunostaining technique, and the hepatic tissue damage, oxidative and inflammatory status biochemical parameters were determined. Results: CCl4 + MTX combined administration produced prominent cirrhotic liver changes, furtherly confirmed by a substantial increase in oxidative stress and inflammatory parameters, whereas mortalities were significantly lower than in other treated groups. Conclusion: The present study introduced a new model that can significantly improve the major limitations of the chemically induced cirrhotic animal models with new pathological features that mimic human cirrhosis. Compared to other chemically induced methods, the present model can save time, cost, and animal suffering.